(3EjQGO GddGd ef EfTGO GdVhGd hEQTGO GdSDGds - (3CHh LYaQ CMeO Hf NGJeI GdCfUGQjs; (3eMeO Hf Ydj Hf gGfF, CHh YHO Gddg, GddNej, GdSHJj, GdZQfGWj,J (B733 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi NU gP GdCeI HGddSGf GdYQHi (B,(3HYO aGdeCehd ai GNJUGQ cJGH GfTGA GdVhGd hEQTGO GdSDGd s
(3BNQgG (B:s
(3hgfG GfJgi eG ChQOJg eeG CedjJ JgPjH ef GdcJGH haUOJg hgh MSHfG hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3dMf GdYGeI dGHf gTGe GddNei JgPjH hJbQjHs
(3hQO GdYfhGf GdCUdi E e (B1 / 133s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs